A comprehensive survey of the Plasmodium life cycle by genomic, transcriptomic, and proteomic analyses. - Hall, N; Karras, M; Raine, J; Carlton, J; Kooij, T; Berriman, M; Florens, L; Janssen, C; Pain, A; Christophides, G; James, K; Rutherford, K; et al. (2005)
Plasmodium berghei and Plasmodium chabaudi are widely used model malaria species. Comparison of their genomes, integrated with proteomic and microarray data, with the genomes of Plasmodium falciparum and Plasmodium yoelii revealed a conserved core of 4500 Plasmodium genes in the central regions of the 14 chromosomes and highlighted genes evolving rapidly because of stage-specific selective pressures. Four strategies for gene expression are apparent during the parasites' life cycle: (i) housekeeping; (ii) host-related; (iii) strategy-specific related to invasion, asexual replication, and sexual development; and (iv) stage-specific. We observed posttranscriptional gene silencing through translational repression of messenger RNA during sexual development, and a 47-base 3' untranslated region motif is implicated in this process.